1981
DOI: 10.1901/jeab.1981.36-51
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Control of Respondent and Operant Key Pecking: A Single Key Procedure

Abstract: Pigeons' responses to a uniformly illuminated response key were either reinforced on a variable-interval one-minute schedule of reinforcement or extinguished for one-minute periods. When 1.5 second signals were presented at the beginning of each compornent, so as to differentially predict reinforcement, the pigeons pecked at the signals, at rates higher than rates during the remainder of the component. When the brief signals were not differentially predictive of reinforcement, pecking in their presence decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
4
13
0
Order By: Relevance
“…Peck rate returned to baseline levels when the S-SR contingency was removed in Phase 3. Similar data were reported by Marcucella (1981). These results, together with the stimulus-specificity of performance changes, indicate that the S-SR contingency, rather than adventitious reinforcement of Component 1 keypecks by Component 2 reinforcers, was responsible for the behavioral effect.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Peck rate returned to baseline levels when the S-SR contingency was removed in Phase 3. Similar data were reported by Marcucella (1981). These results, together with the stimulus-specificity of performance changes, indicate that the S-SR contingency, rather than adventitious reinforcement of Component 1 keypecks by Component 2 reinforcers, was responsible for the behavioral effect.…”
Section: Discussionsupporting
confidence: 86%
“…The relative delay measure and a relative waiting time analysis differ in assumptions about the number of stimulus events participating in the stimulusreinforcer relation, that is, all vs. one. Data relevant to this issue come from a study by Marcucella (1981), who used a procedure similar to that in Experiment I, except that Component 1 of the negative sequence was uncued; that is, the key remained the same color, as in Component 2. Marcucella found that keypecking emerged in Component 1 of the positive sequence whether Component 1 in the negative sequence was differentially cued or not, a finding readily accommodated by a waiting time analysis, as modified for the present study, but not by the relative delay measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcucella (1981) showed that Pavlovian-elicited key pecks in pigeons emerged subsequent to operant discriminative functions, and extinguished first. In that study, elicited key pecks were dissociated from operant key pecks despite comparable reinforcement magnitudes (i.e., between the CS → US and response → reinforcer) that varied only as a function of the operant response.…”
Section: Operant–respondent Interactionmentioning
confidence: 99%
“…Operant and respondent functions of stimuli are often separable. Marcucella (1981), for example, showed that pigeons pecked a key when it was lit briefly with a stimulus that preceded a period of VI reinforcement more often than a different color key that preceded a period of extinction (thus reflecting the respondent relationship between the key and subsequent reinforcement), whereas operant key pecking following the two brief stimulus presentations occurred at nearly the same rate, indicating no discriminative control by the brief stimuli. It may be that further experimentation will allow us to separate the reinforcing from the discriminative and respondent functions of stimuli that signal delays to reinforcement.…”
mentioning
confidence: 99%